Synthesis of an organic phosphoric acid-based multilayered SERS imprinted sensor for selective detection of dichlorophenol. (7th June 2022) - Li, Hongji; Xu, Hongda; Zhang, Jinyue; Li, Yi; Yu, Haochen; Zhao, Yibo; Wang, Dandan; Li, Yunhui; Zhu, Jianwei
Abstract : A novel SERS imprinted sensor (AIM@MIPs) was prepared, which could improve the detection ability of analysis detection. The AIM@MIPs presented sensitive and selective detection property to 2, 6-DCP. Abstract : A novel surface enhanced Raman scattering (SERS) substrate was synthesized by wrapping Ag nanoparticles on the surface of the MIL-101 (Fe) shell under the assistance of IP6, and combining with molecular imprinted polymers (MIPs) for the selective detection of 2, 6-DCP. In this study, as a stabilizer and linking agent, IP6 can form a chemical bond with MIL-101 (Fe) to decrease the distance between two Ag nanoparticles and generate more "hot spots". On the other hand, the inositol hexaphosphate (IP6 ) and MIL-101 (Fe) shell acted as a protective shell layer, preventing Ag nanoparticles from being polluted by the external environment and reduced SERS activity. In addition, the SERS-MIPs can selectively detect the target molecule, avoiding the influence of other interfering substances on the detection effect. The prepared sensor (Ag/IP6 @MIL-101 (Fe)@MIPs, AIM@MIPs) presented sensitive SERS properties, and the detection of limit can reach 10 −9 M. The AIM@MIPs also presented strong selective detection to the target molecules, and can be applied for practical sample detection. This test provides a potential application in the detection of environmental pollutants.